Genetic mapping of QTL for agronomic traits and grain mineral elements in rice - Descalsota-Empleo, Gwen Iris; Amparado, Amery; Inabangan-Asilo, Mary Ann; Tesoro, Frances; Stangoulis, James; Reinke, Russell; Swamy, B.P. Mallikarjuna (Elsevier, 2019)
Malnutrition is one of the prevailing health problems worldwide, affecting a large proportion of the populations in rice-consuming countries. Breeding rice varieties with increased concentrations of elements in the grain is considered the most cost-effective approach to alleviate malnutrition. Development of molecular markers for high grain concentrations of essential elements, particularly Zn, for use in marker-assisted selection (MAS) can hasten breeding efforts to develop rice varieties with nutrient-dense grain. We performed QTL mapping for four agronomic traits: days to 50% flowering, plant height, number of tillers, grain yield, and 13 grain elements: As, B, Ca, Co, Cu, Fe, K, Mg, Mn, Mo, Na, P, and Zn, in two doubled-haploid populations derived from the crosses IR64 × IR69428 and BR29 × IR75862. These populations were phenotyped during 2015DS and 2015WS at IRRI, Los Baños, The Philippines, and genotyped them with a 6 K SNP chip. Inclusive composite interval mapping revealed 15 QTL for agronomic traits and 50 QTL for grain element concentration. Of these, eight QTL showed phenotypic variance of >25% and 11 QTL were consistent across seasons. There were seven QTL co-localization regions containing QTL for more than two traits. Twenty five epistatic interactions were detected for two agronomic traits and seven mineral elements. Several DH lines with high Fe and Zn in polished rice were identified. These lines can be used as donors for breeding high-Zn rice varieties. Some of the major QTL can be further validated and used in MAS to improve the concentrations of nutritive elements in rice grain.